Stability study of flame structure using photodiodes in surface flame burners - Parmis Sadat Jazayeri; Mohammad Zabetian Targhi; Mohammad Reza Karafi (Scientific Reports, 2024)
Abstract Radiation spectroscopy can be effective in identifying pollutants and species. By examining a photodiode, the frequency peaks obtained from the analysis, and the range in which the cell flame is converted to a surface flame, we obtained the value ratio of the cell flame to the surface flame in the range of 0.7–0.74 in different powers. The frequency peak in this range decreases from the maximum value of 9.9823 Hz to its minimum value of 9.058 Hz in different powers. By analyzing the temperature compared to the frequency peak, we found that in the range of equivalence ratio 0.7–0.75, the frequency peak decreases from 9.5 to 9.9 Hz to 8.7–9 Hz. The temperature has an increasing behavior, and in the equivalence ratio, the temperature is in the range of 1400–1500 °C, i.e., at its maximum value. We observed the cell formation process and its conversion to surface flame by flame detection. The flame height in the cellular and superficial regions is in the range of 0.65–0.85, which is the minimum flame height of 3–10 mm, and NO and CO were examined in the ratio of different equations and compared with temperature. In the ratio equivalence ratio of 0.77–0.81 in the temperature range of 1500 °C (maximum), the value of NO is about 16 ppm (maximum), and the value of CO is about 2 ppm (minimum). That is, when the temperature is at its maximum, it becomes CO minimum and NO maximum. This can be used for different applications such as similar and industrial burners.